Analisis Efisiensi Daya Pembangkit Listrik Tenaga Mikrohidro Menggunakan HOMER (Studi Kasus PLTMH Parakandowo Kabupaten Pekalongan) - Siti Suci Murni; Agus Suryanto (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2020)
Microhydro Power Plant (MPP) is a power plant that uses water as a medium to drive turbines and generators. The power generated by PLTMH depends on the flow of river water that flows through PLTMH Prakandowo. In the dry season the water discharge fluctuates so that the efficiency of the MPP has decreased. The research was conducted to analyze the Power Efficiency of MPP Parakandowo. The research method used in this research is non-experimental quantitative using descriptive methods in Parakandowo Hamlet, Sidomulyo Village, Lebakbarang District, Pekalongan Regency. This study provides an overview of the decrease in power efficiency of PLTMH Parakandowo in the dry season. The results of this study are the efficiency value of PLTMH Parakandowo of 65.33% which indicates inefficiency, due to the effect of decreasing water discharge. The long-term solution is to connect MPP with PLN. Homer software can simulate a grid connected MPP with PLN. The simulation results of Homer software hybridize PLTMH with PLN, namely the energy that can be produced is 122,593 kW / year.Keywords—MPP,efficiency,homer,grid connected